STUDY ON SERUM PROCALCITONIN AND SERUM C-REACTIVE PROTEIN IN PULMONARY TUBERCULOSIS PATIENTS, AND ITS ASSOCIATION IN A TERTIARY CARE HOSPITAL, ODISHA: A CROSS-SECTIONAL STUDY. - Meher, Surjya Shankar; Sahoo, Srinibas; Behera, Debasis; Jagaty, Suman kumar; Subhankar, Saswat (Student's Journal of Health Research Africa, 2024)
Background: Pulmonary tuberculosis, a highly contagious bacterial lung infection, remains a significant global health issue. Given its prevalence and impact, this study seeks to analyze the baseline characteristics and distribution of Serum C-reactive protein (Sr. CRP) and Serum Procalcitonin (Sr. PCT) in individuals diagnosed with pulmonary tuberculosis (TB). Additionally, the research aims to elucidate the relationship between Sr. CRP and Sr. PCT levels in individuals with pulmonary TB. Methods: The research consisted of 50 adult individuals diagnosed with pulmonary tuberculosis, with 80% being male and 20% female. The study employed a hospital-based descriptive and cross-sectional study design to evaluate the baseline characteristics and distribution of Serum CRP and Serum PCT levels among the participants. Participation in the study was voluntary, and individuals were required to provide informed consent before being included in the research. Results: Among participants, females had a mean age of 29.70 years (±6.75, range: 21-40 years), while males had a mean age of 43.20 years (±11.88, range: 24-61 years). Sputum microscopy showed most cases at 2+ (50%). Hemoglobin, leukocyte count, CRP, Erythrocyte Sedimentation Rate, and Sr. PCT were significantly associated with Pulmonary Tuberculosis (p<0.001). Neutrophils peaked at 70 (26% of cases), and lymphocytes at 28 (18% of cases). CRP correlated positively with sputum microscopy (p=0.004) and Sr. PCT (p=0.001). Conclusion: The study findings indicate that the concentrations of Serum CRP and Serum PCT among the clinically diagnosed groups of study subjects showed a highly significant association. Moreover, there is evidence of a positive correlation between CRP and Sr. PCT levels, as well as between CRP and sputum microscopy results, in the context of pulmonary tuberculosis. Recommendations: Implement routine screening for serum CRP and PCT levels in diagnosed pulmonary TB patients, enhance TB awareness, and explore CRP and PCT as treatment biomarkers.